1996
DOI: 10.1159/000111420
|View full text |Cite
|
Sign up to set email alerts
|

Proteolipid Protein: Is It More than Just a Structural Component of Myelin?

Abstract: Proteolipid protein (PLP) is the most abundant protein of central nervous system (CNS) myelin. Because of its predicted topography, PLP has been assumed to function as a structural component of myelin, providing stability and maintaining the compact lamellar structure. However, developmental studies have shown that the PLP gene is active long before myelination begins. This and other evidence from various PLP mutants and transgenic models has fueled speculation that PLP or other products of the gene have addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 70 publications
(106 reference statements)
0
36
0
Order By: Relevance
“…Indeed, an overexpression or deficit of PLP gene has been associated with delayed myelination or dysmyelination (37,38). In addition to the structural role, PLP might have some nonstructural role (39). It has been suggested that PLP might regulate differentiation and survival of oligodendrocytes (40 Several possible mechanisms could singly or multiply play a role in the VGB-induced delay in myelination and oligodendroglial cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an overexpression or deficit of PLP gene has been associated with delayed myelination or dysmyelination (37,38). In addition to the structural role, PLP might have some nonstructural role (39). It has been suggested that PLP might regulate differentiation and survival of oligodendrocytes (40 Several possible mechanisms could singly or multiply play a role in the VGB-induced delay in myelination and oligodendroglial cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Although proteins for PL P or its alternatively spliced variant, DM20, are found postnatally at a late stage of oligodendrocyte development (Levine et al, 1990), DM20 mRNA is found at early stages before myelination (Ikenaka et al, 1992;Timsit et al, 1992). The amino acid sequence of PLP is totally conserved among rat, mouse, and human (Mikoshiba et al, 1991); even a point mutation or a slight overexpression of the PLP gene causes severe effects on oligodendrocyte survival (Hudson and Nadon, 1992;Knapp, 1996). The jimpy mouse, one of the PLP mutants, splices out the fifth exon from the PL P mRNA (Nave et al, 1986;Moriguchi et al, 1987).…”
Section: Abstract: Oligodendrocyte Development; Myelin Proteolipid Pmentioning
confidence: 99%
“…The genetic defect in jp has been identified as a point mutation in intron 4 of the myelin proteolipid protein (PLP) gene, resulting in an RNA splice defect which deletes the fifth exon of jp mRNA (Nave et al, 1987a). However, a causal relationship between abherrant PLP and decimation of the OC pool in jp remains unclear (Skoff and Knapp, 1992;Knapp, 1996). Null mutations for PLP demonstrate defective apposition of membrane surfaces in compact myelin but normal myelin content and no sign of OC loss (Boison et al, 1995;Rosenbluth et al, 1996;Klugmann et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…One line of evidence suggests that defective intercellular signaling by astrocytes contributes to the hypomyelinating jp phenotype (Knapp, 1996). In mixed cell type cultures of jp glia, medium conditioned by normal astrocytes, unlike jp astrocytes, enhanced the numbers of OCs that survived and partially restored their myelinogenic phenotype Knapp et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation